Negosiasi Kepercayaan Toriolong Dengan Agama Islam Pada Bissu Dan Masyarakat Bugis Makassar - Nurfadillah Nurfadillah (Departemen Sosiologi Aga,ma, Universitas Islam Negeri Alauddin Makassar, 2019)
This article reviews the old beliefs (toriolong) of the Bugis people and the Bissu community in South Sulawesi. Toriolong's belief in the new modification can still be traced to the present. In the concept of the deity of the Bugis community before the entry of Islam they have had the concept of god in the term Dewata SeuwaE, which is still often heard and believed to exist in that period. Post-Islam entered, the original beliefs of Bugis tribes began to negotiate in order to survive so that the manifestation of old beliefs in the form of rituals or customs still often found in remote areas of Bugis tribes. Like tulakbala, massorong, mappaenre, mattoana, millau bosi, mattedduk arajang, arajang mappedaung, sipulung manre, maddoja bine, mappalili and mappalettuk. Although the ritual is still there, but in essence the ritual has undergone a shift in value and meaning. Because Bugis people have embraced Islam, but the Bugis original customs were not just removed. The survival of the Bissu in South Sulawesi is a remnant of ancient Bugis beliefs that have always been studies of studies that have always tried to be preserved and preserved.